Drivers of nematode diversity in forest soils across climatic zones. Issue 1994 (8th March 2023) - Shao, Yuanhu; Wang, Zuyan; Liu, Tao; Kardol, Paul; Ma, Chengen; Hu, Yonghong; Cui, Yang; Zhao, Cancan; Zhang, Weixin; Guo, Dali; Fu, Shenglei
Abstract : Nematodes are the most abundant multi-cellular animals in soil, influencing key processes and functions in terrestrial ecosystems. Yet, little is known about the drivers of nematode abundance and diversity in forest soils across climatic zones. This is despite forests covering approximately 30% of the Earth's land surface, providing many crucial ecosystem services but strongly varying in climatic conditions and associated ecosystem properties across biogeographic zones. Here, we collected nematode samples from 13 forests across a latitudinal gradient. We divided this gradient into temperate, warm-temperate and tropical climatic zones and found that, across the gradient, nematode abundance and diversity were mainly influenced by soil organic carbon content. However, mean annual temperature and total soil phosphorus content in temperate zones, soil pH in warm-temperate zones, and mean annual precipitation in tropical zones were more important in driving nematode alpha-diversity, biomass and abundance. Additionally, nematode beta-diversity was higher in temperate than in warm-temperate and tropical zones. Together, our findings demonstrate that the drivers of nematode diversity in forested ecosystems are affected by the spatial scale and climatic conditions considered. This implies that high resolution studies are needed to accurately predict how soil functions respond if climate conditions move beyond the coping range of soil organisms.